Architectural History And Media: Caricatures As An Alternative Medium - Çetinel, Meltem (My University, 2019)
The architecture includes not only the built form as a physical existence, but it is also composed of discursive and visual understanding. For discursive and visual practices of architecture, media takes position through all professional, official or popular tools. The media reconstructs the information while conveying it to the public in its own ways. In terms of architecture and media, there is a reciprocal relationship that has an influence on both sides. The media has a transformative effect on the architecture and the value judgments. In other words, media renders the architecture and it transforms the value judgments of the society which also influences architecture in return. It is a kind of vicious cycle which has a bidirectional relationship. The media also documents the architectural culture and makes them immortal. Architectural history is mainly written by using professional documents directly related with the design of buildings and their architects, such as drawings, images, and writings of architects. Hence, historiography commonly focuses on the design of the building and how its architect designs it. However, contemporary architectural history requires sources beyond professional architectural documents to improve the historiography, such as films, posters, caricatures, cartoons, postcards etc. In this study it is aimed to discuss relations of media and architecture briefly and also to underline the variety in media tools. To materialize it analysis of housing production in the mid-twentieth century of Istanbul through caricatures is chosen as a case study of this paper. As a main result of this study, it is aimed to introduce caricatures as an alternative source for architectural historiography.
Keywords: Media; Caricatures; Mid-Twentieth Century Architecture; Architectural Historiography; Housing; Medya; Karikatürler; Yirminci Yüzyıl Ortası Mimarisi; Mimari Tarih Yazımı; Konut